The Influence of Media Cue Multiplicity on Deceivers and Those Who Are Deceived - Xu, Jingjun; Cenfetelli, Ronald T.; Aquino, Karl (2012)
We extend prior research of deceitful behavior by studying the reactions of those who are targets of deception and how a specific attribute of communication media, cue multiplicity, influences such reactions. We report on a laboratory experiment involving dyads asked to engage in a stock share purchase exercise. We find that when a broker is perceived to act deceitfully by the buyer, the buyer reacts with negative affect (anger) which provokes subsequent acts of revenge against the broker. Importantly, we find that media with higher cue multiplicity attenuate buyer anger as well as lessen the propensity for the buyer to seek retaliatory acts of revenge. We further find that moral anger mediates the effect of buyers’ perceived deception on revenge.
Keywords: Interpersonal deception theory (IDT); Revenge; Positive Affect; Moral anger; Deception; Cue multiplicity